decree no. 23/2014 determining the terms and conditions of certain provisions of presidential decree no. 184 for the year 2013 concerning the issuance of customs tariff = قرار وزاري رقم 23 لسنة 2014 بتعديل شروط وأوضاع بعض أحكام قرار رئيس الجمهورية رقم 184 لسنة 2013 بإصدار التعريفة الجمركية / Minister Prime - Egypt. Minister Prime (2025)
Ministry of Finance Decree No. 23 of the year 2014 determining the terms and conditions of certain provisions of presidential decree no. 184 for the year 2013 concerning the issuance of customs tariff – وزارة المالية قرار رقم 23 لسنة 2014 بتحديد شروط وأوضاع بعض أحكام قرار رئيس الجمهورية رقم 184 لسنة 2013 بإصدار التعريفة الجمركية